Pengembangan Komik Akidah Akhlak Untuk Meningkatkan Minat Baca dan Prestasi Belajar Siswa di Sekolah Dasar: Development of Akidah Akhlak Comics to Increase Reading Interest and Student Achievement in Elementary Schools - Fahyuni, Eni Fariyatul; Fauji, Imam (Halaqa: Islamic Education Journal, 2017)
Learning of aqeedah morals at the elementary school is part of the learning of Islam that directs and delivers students have a noble character. Teaching and learning in school during this time, many still rely on textbooks in the form of textbooks, although there have been several variations of the addition of illustrations but neither has a significant influence on the increase reading interest and student learning achievement. From this, appear the idea of researchers to combine an attractive performance of the comic, the plot coherent and easy to understand with textbooks tend textbook. This study aims to produce a attractive aqeedah morals comic, feasible and effective use design research and development include the steps of the research and data collection, planning, early product development, limited testing, and revision of the final product. Techniques validation performed by materials experts, media experts, and conducted limited trials to the students. The final product has different characteristics from other comics, they are : delivery of content aqeedah morals with simple language, the colors clear with animated images and material and matter comic emphasizes the cartoons.